Neuroscience-Based Character Education Management at Raudhatul Athfal Bait Qur'ani: The Quantum Personality Method - Muhammad Al-Husaini Faraj; Nurul Hikmah; Ellys Lestari Pambayun; Muhasyim Muhasyim (Indonesian Journal of Islamic Education Studies (IJIES), 2022)
Character education management based on the personality quantum approach with the Quran in early life is one of the most important predictors of human character formation. The goal of raising well-rounded, intelligent children will never be achieved without strict and practical guidance. This study used a qualitative case study method through field observations and in-depth interviews with leaders, teachers, and parents of students, with field analysis techniques to understand the strategy and management of early childhood character education with the quantum personality method. The result showed that neuroscience-based character education was structured through the curriculum, the preparation of educators, and the availability of adequate infrastructure, which was focused on the formation of cognition and morality of early childhood students. The quantum personality method through management following the Quran could shape students to think more logically and behave positively. The study concludes that the management of early childhood character education with the quantum personality method at Raudhatul Athfal Bait Qur'ani based on neuroscience turns out to have convergence in the learning process in aqliyah (logical thinking) and nafsiyah. This research contributes to a growing body of literature on the potential of neuroscience in the context of character education for young people. Furthermore, it is hoped that it will eventually be recognized as its field of study inside science rather than being dismissed as pseudoscience.